(untitled) (Al-Qamar, 2018)
The Qur’anic questions are also great in terms of importance. The Qur’an also excels in human training. This importance is not only academic or pedagogical but it is the highest of all. It covers every issue of the learner whether it is related to his education, classroom, and life. ALLAH has invited mankind to ponder and reflect in a questioning and inquisitive manner. Those who disobey ALLAH’s command are taught in the verses of the Qur’an that the previous nations were stronger and more powerful than you. The interrogative style in the Qur’an and Hadith also changed the mind of the slave because in the time of Jahiliyyah the slave could not even dare to ask a question in front of the master is also ending. The question is the backbone of education and teaching and learning. Asking a question is half knowledge. Asking a question removes the hesitation of the servant.